Development of Several Types of Banana Peel as an Alternative Edible coating to Increase The Shelf Life of Tomatoes - Runaweri, Christian; Manikome, Nonice; Pinahi, Herodia (Agrikan Jurnal Agribisnis Perikanan, 2024)
Research on the development of several types of banana peels as an alternative edible coating is important to increase the shelf life of tomatoes, the purpose of the study was to produce the best edible coating from the three types of banana peels. Observations were made on changes in the texture of tomatoes and weighing the weight of tomatoes (fruit shrinkage) for 7 days of observation. Weight loss analysis with qualitative methods. The results showed changes in the shape of tomatoes before and after the application of edible coating. From 3 types of banana peels, it was shown that tomatoes that were applied with edible coating had a good texture until the seventh day compared to tomatoes without treatment. The results of the analysis of tomato weight loss showed a difference in the decrease in tomato weight loss, the application of edible coating with goroho banana peels showed the smallest fruit weight loss figure of 0.33 grams, followed by the application of 45% edible coating mulu bebe bananas 0.50 grams and raja bananas 0.83 grams, this is suspected that the pectin content of goroho banana peels is higher than the pectin content in mulu bebe banana peels and raja banana peels. The results of the study obtained good results. This research is good because it can be developed and applied by the community because it is safe for consumers.